LprG-mediated surface expression of lipoarabinomannan is essential for virulence of Mycobacterium tuberculosis. - Rajiv L Gaur (Public Library of Science (PLoS), 2014)
Mycobacterium tuberculosis employs various virulence strategies to subvert host immune responses in order to persist and cause disease. Interaction of M. tuberculosis with mannose receptor on macrophages via surface-exposed lipoarabinomannan (LAM) is believed to be critical for cell entry, inhibition of phagosome-lysosome fusion, and intracellular survival, but in vivo evidence is lacking. LprG, a cell envelope lipoprotein that is essential for virulence of M. tuberculosis, has been shown to bind to the acyl groups of lipoglycans but the role of LprG in LAM biosynthesis and localization remains unknown. Using an M. tuberculosis lprG mutant, we show that LprG is essential for normal surface expression of LAM and virulence of M. tuberculosis attributed to LAM. The lprG mutant had a normal quantity of LAM in the cell envelope, but its surface was altered and showed reduced expression of surface-exposed LAM. Functionally, the lprG mutant was defective for macrophage entry and inhibition of phagosome-lysosome fusion, was attenuated in macrophages, and was killed in the mouse lung with the onset of adaptive immunity. This study identifies the role of LprG in surface-exposed LAM expression and provides in vivo evidence for the essential role surface LAM plays in M. tuberculosis virulence. Findings have translational implications for therapy and vaccine development.